Diversity, seasonality, and antifungal susceptibility of yeasts in the public drinking water supply in a municipality of southeastern Brazil - Brizzotti-Mazuchi, Natalia S.; Cunha, Keith C.; Siqueira, João P.Z.; Almeida, Bianca G. [UNESP]; Lemes, Thiago H. [UNESP]; Maschio-Lima, Taiza [UNESP]; Caetano, Maicon H. [UNESP]; Ribeiro, Mariela D.; Rodrigues, Cláudia R.; Castilho, Elza M.; Almeida, Margarete T.G. (Elsevier, 2020)
The presence of microorganisms in potable water can alter its quality and cause public health issues when ingested or after contact with skin and mucous membranes, especially in individuals with impaired immune system. The aim of this study was to assess the occurrence and seasonality of potentially pathogenic yeast in the public water supply of a municipality in the state of São Paulo, Brazil. In addition, to evaluate the in vitro susceptibility profiles of the isolates against four antifungal drugs. Water samples (n = 1923) were collected from distinct points of the public water system, 15 days after the beginning of each climatic season. They were filtered through a cellulose membrane, which was subsequently upturned on an agar plate. Results show that 11.5% of the samples were positive for yeasts. After identification of the isolates, Rhodotorula minuta was the most prevalent in spring (48.6%), fall (35.2%), and summer (46.3%); and Candida spp. in winter (68.2%). Resistant phenotypes were observed in 54.2% of the isolates, mainly because of Rhodotorula spp. As conclusions, yeasts are present in the water supply during all seasons of the year with great species variability and significant rates of resistance. These results indicate a health concern, suggesting that water quality control protocols require changes to minimize exposure to potentially pathogenic microorganisms and selection of resistant strains.
Keywords: Antimicrobials; Environmental health; Resistance; Water; Yeasts